Cellulose supported poly (amidoxime) Cu/Pd nanoparticles for Aza-Michael and Suzuki-Miyaura reactions - Sultana, Tahnim (2018)
This research is mainly focused on the utility of cellulose supported heterogenous metal catalyst for Aza-Michael and Suzuki-Miyaura reactions. Such reactions are generally conducted by homogeneous catalyst, but the untidy reactions, difficulties in separation of product from reaction mixture, removal and reuse of homogenous catalyst lies as the limitations. Thus, heterogeneous catalysts with different types supports, such as silica gel, metal oxide, organic polymers, graphene and various hybrid inorganic materials have been employed to overcome these issues. Nowadays researchers have developed many economic and environmental sustainable catalytic protocols to develop the process of cross-coupling reactions in green perspective but till now it is difficult to meet the criteria of being safely reusable, non-toxic, chemically sustainable, and organic synthesis catalyst. The development of bio-based materials and composites could be considered as a promising solution of these demerits both in terms of environmental and performances aspects. From this point of view, natural biopolymers (cellulose) could be considered as more acceptable solid support material because it has some promising qualities as widely abundance in nature, bio-degradability, high chemical and mechanical stability, easily chemically modified, bio-renewability, non-toxicity, cheap and environmental friendly. Therefore, cellulose can act as a suitable candidate as solid support for heterogeneous catalytic system. On focusing to this target firstly, cellulose was extracted from waste corn-cob and chemically modified by poly(acrylonitrile). Then resulting polymeric functional group was converted into suitable poly(amidoxime) chelating ligand, followed by treatment with metal (Cu/Pd) salt to afford the related cellulose supported heterogeneous poly(amidoxime) metal complexes. Both complexes were treated with hydrazine hydrate to produce nano-sized cellulose supported poly(amidoxime) copper nanoparticles (CuN@PA) and palladium nanoparticles (PdNs@PA). The characterization and morphological changes were confined by using several spectroscopic techniques such as fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDX), x-ray photoelectron spectroscopy (XPS), x-ray powder diffraction (XRD), ultraviolet-visible spectrophotometry (UV-vis), thermogravimetric analysis (TGA) and inductively coupled plasma atomic emission spectroscopy (ICP-AES) analyses. The dark brown coloured CuN@PA (size- 6.8 ± 2 nm) was efficiently catalyzed Aza-Michael reaction of aliphatic amines with different olefins to afford the corresponding alkylated products up to 96% at room temperature. Whereas PdNs@PA (size- 2.8 ± 6 nm) showed high catalytic performance towards Suzuki-Miyaura cross-coupling reaction of aryl halides with organoboronic acids to give the corresponding biaryl products up to 95% yield with high turnover number (TON) 16250 and turnover frequency (TOF) 5416 h-1. In both reactions, the cellulose supported nanoparticles were easy to recover and reused several times without a significant loss of their activity. Thus, a bio-based and effective cellulose supported heterogeneous metal catalyst was prepared from completely waste material (corn-cob) and applied efficiently to two popular reaction, Aza-Michael and Suzuki-Miyaura reactions. This cellulose supported metal catalyst would be a great achievement not only in the green industrial aspect but also a variety of natural products can be synthesized by using heterogeneous catalyzed key step reaction.